(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Six varieties of spring wheat such as Mayoor, Sebia, Prodip, Bulbul, Bijoy, Sowgat were crossed with a single maize variety Pop corn as pollinator. Fertilization of wheat eggs, formation, retention and development of haploid embryos were facilitated by the application of 2, 4-D at 100ppm.The haploid embryos were cultured on MS medium, which regenerated haploid plants. Highly significant variations were observed for the characters related to haploid production such as development of caryopsis, recovery of embryos and regeneration of haploid plants over total pollinated florets. The highest caryopsis setting over pollinated florets was noticed in the variety Sebia. Recovery of embryos over caryopsis was the highest in the variety Bijoy. Germination of embryos over total embryos and regeneration of haploid plants over total pollinated florets were highest in the variety Mayoor. At the time of embryo rescue, occurrence of more than one embryo in a single caryopsis were noticed which were considered as polyembryos. Generation of multishoot from attached polyembryos (appeared as single embryo) was also considered as polyembryos. Highly significant variations were observed among the six varieties of wheat for formation of polyembryos over caryopsis, germination of polyembryos over total embryos and formation of polyembryos accounted to multishoots over total embryos. The highest number of polyembryos formation and germination of polyembryos were observed in the variety Mayoor. The varieties Sebia and Mayoor gave the highest polyembryos formation accounted to multishoots which were more than 8.00%. DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17035